Influence of Leadership Styles and Work Orientations on Employee Performance in the Jakarta Islamic Banking Industry - Edy, Junaedi (2023)
Leadership styles can have both positive and negative effect on employee performance, and the effectiveness of a particular style depends on the organization‘s goals, the leader‘s personality, and the dynamics of the team. Appropriate leadership styles is a critical factor in employee performance. The study aims to investigate the effect of leadership styles and work orientations on employee performance within the Jakarta Islamic banking industry. The research design used for this study is descriptive. A pilot test was carried out prior to data collection to confirm the validity and dependability of the study instrument. This study used a questionnaire and a field survey to gauge employee performance. Using a purposive sampling technique, a total of 364 employees Islamic banks, from sample 12 commercial Islamic bank and sharia business unit. PLS-SEM was employed for the data analysis. The findings of the study that leadership styles both situational leadership and path goal leadership, both of which have a positive and significant effect on employee performance. The findings also demonstrate that work orientation, which has a favorable and significant effect on the performance of Islamic bank employees. This study suggests that leaders in Islamic banks should encourage positive innovation and creativity, leaders are willing to listen to employees' expectations and are willing to discuss with employees to achieve better performance.